2020
DOI: 10.3390/foods9101516
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Nutrient Composition of Seafood from North West Africa: Implications for Food and Nutrition Security

Abstract: Fish and seafood may play an important role for nutrition and food security as they contain essential vitamins, minerals, and essential fatty acids. The aim of this study was to describe the nutrient composition, including fatty acids, amino acids, vitamins, and minerals, in commonly consumed fish species (fillet- and whole fish samples) sampled off the Northwest African coast. Furthermore, we assessed the species’ contributions to the recommended nutrient intake (RNI) values from the World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…As Thilsted et al (1997) emphasized 25 years ago, consuming a variety of small fish species that when combined contained many different micronutrients, has proven to be highly beneficial for nutrition and health. A 100-g portion of raw anchovies (whole fish)-the most common species sold by the traders (Table 2)-covers the daily recommended nutrient intake of vitamins B12 (adult women), and approximately 40-60% the recommended intake of vitamin D, calcium, zinc, and the long-chained marine n-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (Aakre et al 2020). Studies from Sri Lanka and north-west Africa have documented that whole fish are in general more nutrient dense than fish fillet for most nutrients; for example, a horse mackerel fillet would cover less than 10% of the daily recommended intake of calcium, zinc, iron, vitamin A, and the n-3 fatty acids EPA and DHA (Aakre et al 2020;Reksten et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As Thilsted et al (1997) emphasized 25 years ago, consuming a variety of small fish species that when combined contained many different micronutrients, has proven to be highly beneficial for nutrition and health. A 100-g portion of raw anchovies (whole fish)-the most common species sold by the traders (Table 2)-covers the daily recommended nutrient intake of vitamins B12 (adult women), and approximately 40-60% the recommended intake of vitamin D, calcium, zinc, and the long-chained marine n-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (Aakre et al 2020). Studies from Sri Lanka and north-west Africa have documented that whole fish are in general more nutrient dense than fish fillet for most nutrients; for example, a horse mackerel fillet would cover less than 10% of the daily recommended intake of calcium, zinc, iron, vitamin A, and the n-3 fatty acids EPA and DHA (Aakre et al 2020;Reksten et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Animal-based foods such as red meat, eggs, cheese, fish and seafood have relatively high Zn contents, where 100 g can provide up to 40% of the recommended daily Zn intake [ 73 ]. In addition to Zn, meat, fish and seafood contain bioavailable calcium, Fe, iodine, vitamin A, essential fatty acids and amino acids, including lysine and tryptophan [ 74 ]. It has been reported that 100 g of whole fish contribute significantly to the RDA for several nutrients, although nutrient composition varies with fish type, habitat and season [ 74 ].…”
Section: Strategies To Alleviate Vitamin a Zinc And Protein Malnumentioning
confidence: 99%
“…In addition to Zn, meat, fish and seafood contain bioavailable calcium, Fe, iodine, vitamin A, essential fatty acids and amino acids, including lysine and tryptophan [ 74 ]. It has been reported that 100 g of whole fish contribute significantly to the RDA for several nutrients, although nutrient composition varies with fish type, habitat and season [ 74 ]. Plant-based foods such as chickpeas, lentils and beans also contain substantial amounts of Zn and essential amino acids [ 75 ].…”
Section: Strategies To Alleviate Vitamin a Zinc And Protein Malnumentioning
confidence: 99%
“…Marine seafood has been an integral part of the human diet throughout humankind history and has been correlated since then with a healthy diet and the well-being of humans [1]. Fish and seafood play a key role in human nutrition due to their high content in essential nutrients [2]. Marine mollusk-bivalves are considered to be also a nutritious diet, as they contain high quality of protein and minerals, low lipid content, and high concentration of polyunsaturated fatty acids (PUFAs) [3].…”
Section: Introductionmentioning
confidence: 99%